Otimização multicritério para despacho econômico e ambiental de usinas térmicas utilizando enxame de partículas - AZEVEDO, Raimundo Edney dos Santos (Universidade Federal do Pará, 2017)
One of the main objectives in the generation of electricity in thermal systems is to minimize fuel consumption through optimal allocation of power generation for each generating unit via the economic dispatch, maintaining pollutant emissions within the limits of environmental licensing, whose integrated solution is subject to a set of equality and inequality constraints. Due to environmental concerns that were developed from the emissions produced by power plants that use fossil fuels, the economic dispatch that minimizes only the total fuel cost can no longer be considered a suitable option of dispatch. This paper therefore proposes a strategy based on mathematical models to solve the problem of load dispatch considering the economic problems and the emission of pollutants, whose premises are combined into an objective function and several electrical and emission constraints using the LabView software environment. The results achieved with the application of the procedures proposed here to a thermal power plant in the city of Manaus AM, appear quite positive towards providing dispatch solutions that proved sustainable with regard to the economic and environmental aspects considered.